According to the scriptures the death of Christ in the Old Testament and the New - Allen, David M. 1972- (SCM Press, 2018)
"If all you know is the New Testament, you do not know the New Testament" - so the late New Testament scholar Martin Hengel is reputed to have said. According to the Scriptures considers the way in the New Testament writers utilized the Jewish Scriptures in order to describe, articulate and evaluate the death of Jesus, takes Hengel at his word. What Old Testament texts are quoted in the New Testament, how are they used and what might such analysis mean for the (contemporary) reader? Focusing in particular on the passion narratives in the Synoptic Gospels, According to the Scriptures seeks to engage with these questions. It will provide a useful new framework for thinking about why the early Church understood Jesus' death in terms of the Scriptures, what difference that understanding made, and what relevance that might have for us as we seek to make sense of the death of Jesus
Keywords: Bibel -- Neues Testament; Tod Jesu; Bibel -- Altes Testament; Jesus Christ / Crucifixion; Jesus Christ / Passion; Jesus Christ; Passion narratives (Gospels) / Criticism, interpretation, etc; Crucifixion of Jesus Christ; Passion narratives (Gospels); Passion of Jesus Christ; Criticism, interpretation, etc